Prevalence and stabilizing trends in overweight and obesity among children and adolescents in China, 2011-2015 - Jiguo Zhang; Huijun Wang; Zhihong Wang; Wenwen Du; Chang Su; Ji Zhang; Hongru Jiang; Xiaofang Jia; Feifei Huang; Yifei Ouyang; Yun Wang; Bing Zhang (BMC, 2018)
Abstract Background The prevalence of childhood overweight and obesity in developed countries appears to be plateauing. The purpose of this study was to provide the most recent data on the prevalence and trends in overweight and obesity among Chinese children and adolescents from 2011 to 2015. Methods We used data collected in the China Health and Nutrition Survey (CHNS) and China Nutritional Transition Cohort Study (CNTCS). We used two waves of the survey in 12 provinces conducted in 2011 (aged 7-18 years; n = 1458) and 2015 (aged 7-18 years; n = 1084) to perform a trend analysis. We used data collected in 15 provinces (aged 7-18 years; n = 1617) to estimate the prevalence of overweight and obesity among Chinese children and adolescents in 2015. Results In 2015, based on the Working Group for Obesity in China (WGOC) criteria, the prevalence of overweight and obesity were 14.0% (95% CI, 11.6-16.3) and 10.5% (95% CI, 8.4-12.6) in boys, and 9.7% (95% CI, 7.7-11.8) and 7.1% (95% CI, 5.2-8.9) in girls, respectively. The increase in BMI z-scores from 2011 to 2015 was statistically significant among adolescents (p = 0.0083), but not among children. No significant changes were observed in prevalence of overweight and obesity between 2011 and 2015, excepting adolescents aged 12-18 years (p = 0.0086). Conclusions Since 2011, overweight has remained stable, and obesity has stabilized in children, though not in adolescents. Although levels of childhood overweight and obesity in China are not high compared to other developed countries, they remain concerning enough that effective policies and interventions need to be sustained and intensified for lowering rates of childhood overweight and obesity.